A synoptic map of halo substructures from the Pan-STARRS1 3π survey. Issue 2 (24th August 2016) - Bernard, Edouard J.; Ferguson, Annette M. N.; Schlafly, Edward F.; Martin, Nicolas F.; Rix, Hans-Walter; Bell, Eric F.; Finkbeiner, Douglas P.; Goldman, Bertrand; Martínez-Delgado, David; Sesar, Branimir; Wyse, Rosemary F. G.; Burgett, William S.; et al.
Abstract: We present a panoramic map of the entire Milky Way halo north of δ -30^° (∼30 000 deg 2 ), constructed by applying the matched-filter technique to the Pan-STARRS1 3π Survey data set. Using single-epoch photometry reaching to g ∼22, we are sensitive to stellar substructures with heliocentric distances between 3.5 and ∼35 kpc. We recover almost all previously reported streams in this volume and demonstrate that several of these are significantly more extended than earlier data sets have indicated. In addition, we also report five new candidate stellar streams. One of these features appears significantly broader and more luminous than the others and is likely the remnant of a dwarf galaxy. The other four streams are consistent with a globular cluster origin, and three of these are rather short in projection (\!\! 10^° ), suggesting that streams like Ophiuchus may not be that rare. Finally, a significant number of more marginal substructures are also revealed by our analysis; many of these features can also be discerned in matched-filter maps produced by other authors from SDSS data, and hence they are very likely to be genuine. However, the extant 3π data is currently too shallow to determine their properties or produce convincing colour–magnitude diagrams. The global view of the Milky Way provided by Pan-STARRS1 provides further evidence for the important role of both globular cluster disruption and dwarf galaxy accretion in building the Milky Way's stellar halo.